Quality and Timing of Stressors Differentially Impact on Brain Plasticity and Neuroendocrine-Immune Function in Mice. (31st March 2013) - Capoccia, Sara; Berry, Alessandra; Bellisario, Veronica; Vacirca, Davide; Ortona, Elena; Alleva, Enrico; Cirulli, Francesca
Abstract : A growing body of evidence suggests that psychological stress is a major risk factor for psychiatric disorders. The basic mechanisms are still under investigation but involve changes in neuroendocrine-immune interactions, ultimately affecting brain plasticity. In this study we characterized central and peripheral effects of different stressors, applied for different time lengths, in adult male C57BL/6J mice. We compared the effects of repeated (7 versus 21 days) restraint stress (RS) and chronic disruption of social hierarchy (SS) on neuroendocrine (corticosterone) and immune function (cytokines and splenic apoptosis) and on a marker of brain plasticity (brain-derived neurotrophic factor, BDNF ). Neuroendocrine activation did not differ between SS and control subjects; by contrast, the RS group showed a strong neuroendocrine response characterized by a specific time-dependent profile. Immune function and hippocampal BDNF levels were inversely related to hypothalamic-pituitary-adrenal axis activation. These data show a fine modulation of the crosstalk between central and peripheral pathways of adaptation and plasticity and suggest that the length of stress exposure is crucial to determine its final outcome on health or disease.